COVID-19, Inequality and Older People Everyday Life during the Pandemic - Lewis, Camilla (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book provides new insights into the challenges facing older people in the context of the COVID-19 pandemic. It draws upon novel qualitative longitudinal research which recorded the experiences of a diverse group of people aged 50+ in Greater Manchester over a 12-month period during the pandemic. The book analyses their lived experiences and those of organisations working to support them, shedding light on the isolating effects of social distancing. Focusing on interviews with 21 organisations, as well as 102 people from four ethnic/identity groups, the authors argue that the pandemic exacerbated existing inequalities in the UK, disproportionately affecting low-income neighbourhoods and minority ethnic communities. The book outlines recommendations in relation to developing a 'community-centred approach' in responding to future variants of COVID-19, as well as making suggestions for how to create post-pandemic neighbourhoods.